engaruh Video Animasi Bermuatan Moral terhadap Kemandirian pada Anak Usia 5-6 Tahun - Kurniawati, Asih Budi; Safitri, Leny Aam; Sugiana, Sugiana (Efektor, 2024)
A spectacle is often used as guidance, one of the positive and educational spectacles is an animated video. Through video animation children not only fantasize or imagine, but can see and imitate it. The formation of independence is very important, because if taught from an early age it will be well embedded. Therefore, the provision of animated videos can be done to stimulate independence in early childhood. The purpose of this study was to determine the effect of video animation on independence in children aged 5-6 years. This study uses quantitative research with pre-experimental design. The method used is one-group pretest-posttest design. There is a positive influence of video animation on the independence of children aged 5-6 years. The difference in the results of the average ability of children before and after treatment using video animation is 11.29, meaning that video animation can be used as a learning medium to stimulate independence in children aged 5-6 years.